Chemical characterization and oxidative stability of olive oils extracted from olive trees of Southern Brazil - Bruscatto, Mariângela Hoffmann; Zambiazi, Rui Carlos; Crizel-Cardoso, Michele; Piatnicki, Clarisse Maria Sartori; Mendonça, Carla Rosane Barboza; Dutra, Fabiana Lemos Goularte; Coutinho, Enilton Fick (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to characterize the chemical composition of olive (Olea europaea) oils produced in Southern of Brazil and correlate it with oxidative stability. Olive oils from the Arbequina, Coratina, Frantoio and Koroneiki cultivars were evaluated. A completely randomized experimental design was used, in a uniform arrangement, with three replicates. Acidity value, peroxide index, specific absorption, tocopherol content, phenolic compound content, carotenoid content, chlorophyll content, fatty acid profile, and oxidative stability were determined. The oils from the Coratina and Frantoio cultivars were classified as extra virgin-oils. The olive oil from the Coratina cultivar showed the highest levels of pigments, followed by the oil from Koroneiki. The oil from the Coratina cultivar also presents higher contents of phenolic compounds (1,725.5 mg kg-1) and tocopherols (437.8 mg kg-1). The major fatty acid in all samples is oleic acid.